Performance assessment of parabolic trough collector (ptc) by using three passes receiver for preheating the fuel oil under Iraq climate for different mass flow rates - Abbas, Mohammed Saad; Azwan, Sapit; Baqer, Nawfel M.; Balla, ,Hyder H.; Hayder, Ali Mohammed (2019)
An alternative design receiver of parabolic trough collector (PTC) has been discussed in the present study. The three passes design (3p) receiver made from copper and coated with selective black paint was studied and optimized experimentally. Mass flow rates were varied alongside number of days. The proposed design was compared with the PTC equipped with smooth receiver (SM). The aforementioned variations resulted in the experiments performed in September 2018. The 17th, 18th, 19th, and 20th, were chosen for the PTC with smooth receiver, while 25th , 26th, 27th, and 28th were for the receiver with three passes). The solar irradiances for these days were similar. The heat transfer fluid (HTF) was fuel oil. Mass flow rates of 2, 2.5, 3, 3.5 LPM were observed alongside change in number of days for the experiment. The results show that the PTC with three passes receiver achieved higher average thermal efficiency and average useful energy than the PTC with smooth receiver.